Masker Wajah Peel-Off Tanaman Krokot Terhadap Jerawat Nodul - Nurulisma Saputri; Afta Nisa Mahetin (Garina, 2023)
Purslane plant is an herbal plant that is used as a medicine for skin infections. The author is interested in using the purslane plant as a peel-off mask to relieve acne nodules. The aim is to find out how to manufacture, sensory test results, public test results, and determine the effect of the purslane peel-off mask. This research was conducted with the methods of observation, experimentation, documentation, interviews, questionnaires, literature. The analysis used is descriptive qualitative analysis. The manufacture of purslane powder starts from the preparation of tools, materials, cleaning, drying, and refining. The manufacture of peel-off masks begins with the preparation of tools, materials, weighing, mixing, heating, and packaging. The feasibility of the product is tested based on color, aroma, texture, adhesion, product appearance. Product improvement is the addition of essence to the peel-off mask. In conclusion, according to the validator, the purslane plant powder is suitable for use in making peel-off masks and the results of the purslane peel-off mask facial treatment can relieve acne nodules. Suggestions for further researchers to change purslane plant powder into oil extract to maintain its content, BPOM test, and laboratory tests.